Longitudinal relations between future planning and adolescents' academic achievement in China. (August 2019) - Zhao, Jingxin; Li, Ruijuan; Ma, Jinling; Zhang, Wenxin
Abstract: Introduction: Planning for the future is important for adolescents' development and academic adaptation. Most prior research has focused primarily on the effects of future planning on adolescents' academic achievement, and there is a dearth of literature examining the effects of adolescents' academic achievement on their future planning. The current study examined the longitudinal reciprocal relations between adolescents' future planning and academic achievement in China. Methods: The study sample consisted of 775 Chinese junior high school students (391 boys, 384 girls; M age  = 13.38 years, SD  = 0.89). Future planning and academic achievement were measured at three time points that were equally spaced by a 6-month lag. Path analyses with cross-lagged effects were used to examine the longitudinal reciprocal relations between adolescents' future planning and academic achievement. Results: The associations between future educational planning and academic achievement were reciprocal. Future occupational commitment predicted adolescents' academic achievement, and academic achievement predicted adolescents' affects concerning future occupation. However, there was no significant association between future occupational exploration and academic achievement. Moreover, these patterns of longitudinal relations applied equally to boys and girls, and younger and older adolescents. Conclusions: The reciprocal relations between future planning processes and academic achievement differed across domains (e.g., educational and occupational domains). These findings suggest that future planning may be a protective factor for improving adolescents' academic achievement, and high academic achievement may also be beneficial for Chinese adolescents' future planning.